A study of covid-19 recession on the housing prices in Johor Bahru - Tee, Yee Yang (2022)
This study adopts data visualization techniques to investigate the impact of the COVID-19 recession on the housing market in Johor Bahru, Malaysia. This study employs data from the period January 2018 – November 2021. Based on the findings, a huge recession on housing market in Johor Bahru was observed. The transaction volume during pandemic is decreasing over time as well as the total transacted price for residential property. Some macroeconomic indicators possess relationship with the housing market in Johor Bahru. Exchange rates and interest rates are positively related with property market while inflation rates and unemployment rates are possessing negative relationship on it. Moreover, buyers have slightly more interest on landed or low-rise buildings in Johor Bahru during pandemic.